The Influence of Service Quality, Platform Ease and Price on Shopeefood Customer Satisfaction in Tangerang City - Gilang Damarjati Sasongko (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of service quality, platform convenience, and price on Shopeefood customer satisfaction in Tangerang City. The data collection technique was carried out using a Likert-scale questionnaire which was distributed online on the Google form. This test was carried out using multiple linear regression analysis method. Data were taken from 140 respondents and analyzed using SPSS. Respondents were taken from Shopeefood users who live in Tangerang City. Based on the results of the study it was found that service quality and price had a positive effect on customer satisfaction and platform ease had no effect on customer satisfaction